An Appropriate Population for Acute Inpatient Rehabilitation? A Case Series of Three Patients With Advanced Heart Failure on Continuous Inotropic Support. Issue 6 (21st January 2015) - McCormick, Zachary L.; Chu, Samuel K.; Goodman, Daniel; Oswald, Matthew; Reger, Christopher; Sliwa, James
Abstract: The number of individuals with heart failure and the treatment modalities available to manage heart failure are increasing. Continuous inotropic support is a treatment modality used in cases of severe heart failure. Although most patients initiated on continuous inotropic support are discharged home, those with greater functional compromise, comorbid conditions that cause disability, or other significant medical complexity may be referred to acute inpatient rehabilitation. The feasibility and benefits of acute inpatient rehabilitation in this population, however, has yet to be investigated. We report the functional progress and medical complications of 3 patients on continuous inotropic support who participated in acute inpatient rehabilitation. The patients demonstrated varying levels of success, highlighting a need for evidence‐based, preadmission screening criteria for this population.